Faktor yang Mempengaruhi Kepuasan dan Niat Pembelian Ulang dengan Peran Moderasi Biaya Peralihan dan Komitmen Perbankan Digital - Putra, Edy Yulianto; Tan, Elvy; Purwianti, Lily (Jurnal Samudra Ekonomi dan Bisnis, 2025)
The study aims to examine the impact of service quality, reputation, customer trust, price perception, satisfaction, switching costs, and commitment on the repurchase intentions of digital banking app users. The research targets digital banking app users who remain uncertain about trust, reputation, and satisfaction. The findings indicate that service quality, reputation, and customer trust significantly affect customer satisfaction, while price perception has no significant impact due to the minimal cost differences among digital banking services. Service quality, reputation, and trust indirectly influence repurchase intentions through satisfaction as a mediating variable. Switching costs were found to moderate the relationship between satisfaction and repurchase intentions, while commitment does not. This suggests that customer satisfaction directly affects repurchase intentions without the need for commitment as a moderating variable.